Preparation method of large-particle high-stability pruss blue
Patent Information
- Application Number
- CN202611450142.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
悬浮液分层问题:行业传统工艺普遍采用固体碳酸钠配制悬浮液,反应速率慢、液态二氧化硫消耗量大;目前行业也逐步采用焦亚硫酸钠与二氧化硫配制悬浮液,但该类悬浮液极易出现固液分层
[0022]本发明具有如下的有益效果:通过悬浮液均质化、多点pH调控、环氧乙烷抑副、梯度结晶、复配醇醚助剂增粒多技术协同,产生叠加增效效果,具备突出的创造性与实用性,具体有益效果如下:通过原料粉碎、半插底管、强化搅拌的组合手段,彻底消除悬浮液固液分层,合成初期晶核纯净均一,晶体致密性提升40%,杜绝原料杂质夹杂问题,产品基础纯度提升4~5个百分点。
Smart Images

Figure CN122957795A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic sulfide preparation technology, and in particular to a method for preparing large-particle, highly stable sodium hydrosulfite. Background Technology
[0002] Sodium dithionite (Na2S2O4) is a strong reducing agent used in large quantities in the industrial field. Currently, the mainstream industrial production process is the sodium formate process, which has advantages over the traditional zinc powder process, such as lower raw material costs and no heavy metal pollution.
[0003] The existing sodium formate method for preparing sodium dithionite has the following drawbacks: Suspension stratification: Traditional industry processes commonly use solid sodium carbonate to prepare suspensions, resulting in slow reaction rates and high consumption of liquid sulfur dioxide. Currently, the industry is gradually adopting sodium metabisulfite and sulfur dioxide for suspension preparation, but these suspensions are highly prone to solid-liquid stratification. When the batching vessel uses a direct-insertion bottom pipe for feeding, the solid at the bottom enters the synthesis vessel first, easily causing impurities from the raw materials to be mixed into the crystals. Later, concentrated feeding of the liquid phase leads to excessively high local acidity in the system, triggering the decomposition of sodium dithionite, ultimately resulting in a loose crystal structure, small particle size, and high dust content.
[0004] pH and Byproduct Control Defects: The pH of the synthesis reaction is a core parameter determining product quality. Current processes often use single-point addition of sulfur dioxide, which easily leads to localized pH imbalances. When pH < 4.4, the high-temperature decomposition of sodium dithionite intensifies; when pH > 4.6, the main reaction kinetics are insufficient, and the raw material conversion rate decreases. Trace decomposition of sodium dithionite produces sodium thiosulfate, a substance with strong catalytic activity that continuously accelerates the decomposition of sodium dithionite. The industry recognizes a sodium thiosulfate concentration of 15 g / L as a critical danger threshold; exceeding this concentration will cause a significant reduction in product yield or even complete decomposition. Even if traditional processes can control the sodium thiosulfate concentration below 15 g / L (approximately 7.9 g / L under normal operating conditions), this concentration still significantly reduces the main reaction rate and inhibits normal crystal growth, resulting in low product purity, small particle size, and insufficient conversion rate—a core bottleneck restricting product quality improvement.
[0005] Product particle size and stability defects: Traditional drying processes only use methanol washing and sodium carbonate stabilization treatment, without particle modification methods. The finished product is mainly fine powder with a large specific surface area. When exposed to air, it is easily oxidized and decomposed to produce sulfur dioxide, which not only poses serious dust pollution, but also has the safety hazard of spontaneous combustion. Traditional products have a shelf life of only 6 months under normal temperature and sealed conditions. During storage, the reducing power decays rapidly, and fine particles are prone to secondary pulverization, making them unsuitable for complex application scenarios such as high temperature and high humidity.
[0006] Environmental and safety shortcomings: During the production and use of fine particulate products, dust flies around and sulfur dioxide is emitted in large quantities without organization, which is harmful to the health of operators and does not meet the requirements of green chemical production.
[0007] Current improvements are mostly focused on increasing particle size or pH control, with limited technical means and no synergistic effect between processes. Problems such as easy particle re-fineness, unstable control of by-products, and short shelf life still exist, making it difficult to achieve integrated production of large particles, low dust, high stability, and long shelf life. Therefore, developing a multi-process synergistic optimization method for preparing large-particle, highly stable sodium dithionite that can be applied on a large scale has significant industrial value and environmental significance. Summary of the Invention
[0008] Based on the technical problems existing in the background art, the present invention proposes a method for preparing large-particle, highly stable sodium hydrosulfite.
[0009] This invention proposes a method for preparing large-particle, highly stable sodium hydrosulfite, comprising a batching process, a synthesis reaction process, a crystallization and aging process, a filtration and washing process, a drying process, and a finished product blending process. The entire process is under nitrogen inert protection, and the reaction medium is a mixture of methanol and deionized water at a mass ratio of 80:20. The batching process involves preparing an AME suspension using sodium metabisulfite and liquid sulfur dioxide, and an AE suspension using sodium formate. Both suspensions are then homogenized to prevent stratification. The synthesis reaction process employs online pH monitoring combined with a multi-point distributed dropping method to control the pH of the reaction system to 4.4–4.6, while simultaneously adding ethylene oxide to the reaction system. The ethylene oxide is added at 1.0–1.5 times the stoichiometric ratio of the estimated sodium thiosulfate production, controlling the sodium thiosulfate concentration in the synthesis filter press filtrate to 3.0 g / L or below. The estimated sodium thiosulfate production is determined based on the theoretical calculation value of a main reaction by-product rate of 3%–5%, or by real-time back-calculation based on the measured sodium thiosulfate concentration in the previous batch synthesis filter press filtrate. The drying process involves adding a compound alcohol ether additive to the wet sodium dithionite to increase the particle size of the product and reduce dust generation.
[0010] Synthetic Filtration Filtrate: The liquid phase fluid directly discharged after nitrogen pressure filtration of the sodium dithionite synthesis suspension to separate the wet solid sodium dithionite; originating from the synthesis-pressure filtration process, it contains methanol-water solvent, unreacted raw materials, sodium thiosulfate, Bunter salt and other dissolved components; it has not undergone filtration to remove impurities, alcohol-water ratio adjustment and pH calibration, and is the original liquid phase produced by the process, and cannot be directly returned to the batching tank for feeding.
[0011] Methanol washing waste liquid: Sodium dithionite wet cake obtained by nitrogen pressure filtration is washed with anhydrous methanol. The waste liquid flowing out after washing has a high methanol content and carries salt impurities carried on the surface of the wet cake. It belongs to the original liquid phase of the process output and cannot be directly returned to the batching tank for feeding.
[0012] Recycled preparation solution: The synthetic pressure filtrate and methanol washing waste liquid are collected and mixed, filtered to remove impurities, the methanol-water ratio is adjusted to the required 80:20, and the pH is calibrated to obtain qualified liquid material. This material is stored in a special storage tank and can be directly added to the batching kettle to prepare AE suspension. During the recycling process, sodium thiosulfate and Bunter salt will gradually accumulate. Every 15-20 batches of production operation, some of them need to be discharged and fresh methanol-water medium is added to prevent salt saturation precipitation.
[0013] Preferably, in the batching process, the raw materials are in the following mass ratio: sodium formate: sodium metabisulfite: liquid sulfur dioxide = 1.2:1:0.8; When preparing AE suspension, add 60% of the previous batch of recycled preparation liquid and industrial-grade sodium formate to No. 1 batching vessel, add deionized water to adjust the alcohol-water ratio to 80:20, stir and preheat to 65°C. When preparing the AME suspension, sodium metabisulfite and liquid sulfur dioxide are added to the No. 2 batching vessel, and the pressure inside the vessel is controlled at 0.2MPa~0.3MPa and the system temperature is ≤15℃.
[0014] Preferably, the suspension homogenization and anti-stratification pretreatment includes: using an air jet mill to pulverize the agglomerated sodium formate and sodium metabisulfite, with the raw material particle size controlled at 80μm to 120μm; modifying the traditional straight-insertion bottom pipe of the batching vessel into a semi-insertion bottom discharge pipe, with the discharge pipe outlet installed at 1 / 3 to 1 / 2 of the static liquid level in the vessel; prioritizing the extraction of the suspension from the uniform solid-liquid region in the middle of the batching vessel for feeding during the synthesis feeding stage; and maintaining the stirring speed at 120r / min to 150r / min throughout the process.
[0015] Preferably, the synthesis reaction process is carried out in a stainless steel pressure reactor, which is pre-purified with industrial high-purity nitrogen with a purity of ≥99.99% until the oxygen content inside the reactor is <0.1%; Simultaneously, AE suspension and AME suspension are introduced into the synthesis reactor, and the reaction system temperature is controlled at 78℃~83℃, the reaction pressure at 0.15MPa~0.25MPa, the stirring speed at 80r / min~120r / min, and the total feeding time is 2h~3h.
[0016] Preferably, the multi-point distributed dripping method is as follows: the liquid sulfur dioxide is changed from the traditional single-tube dripping to a 3-5 point distributed micro-dripping method, the dripping pipeline is made of polytetrafluoroethylene corrosion-resistant material, and the dripping points are evenly distributed along the side wall of the synthesis reactor. In conjunction with an industrial online pH meter, samples are taken every 30 minutes for testing. An immersion-type industrial online pH electrode is used for continuous real-time monitoring. Sodium thiosulfate cannot be continuously monitored in real time, so manual sampling is required every 30 minutes. The pH is also tested during sampling, and the sulfur dioxide drop acceleration rate is finely adjusted in real time to control the pH fluctuation range of the reaction system within ±0.2. The production process is set with a pH warning range of 4.3 to 4.8. When the pH exceeds this warning range, the acceleration rate of liquid sulfur dioxide droplets is adjusted immediately.
[0017] Preferably, the ethylene oxide is added dropwise at a uniform rate from the initial stage of the synthesis reaction, and all addition is completed within the first 1 / 3 of the total reaction time; the ethylene oxide reacts with sodium thiosulfate to form Bunter salt, which blocks the catalytic decomposition of sodium dithionite by sodium thiosulfate.
[0018] Preferably, the crystallization aging process is as follows: after the synthesis reaction is completed, the temperature is kept at 30 min. After the pH value stabilizes and no longer changes, the temperature is slowly reduced to 45℃~50℃ at a rate of 1℃ / min~2℃ / min, and the temperature is kept constant for 1 hour to promote the full growth and densification of sodium dithionite crystals.
[0019] Preferably, the filtration and washing process uses nitrogen pressure filtration to separate the solid wet product from the synthetic pressure filtrate, with a pressure of 0.1 MPa to 0.2 MPa. The wet sodium dithionite after pressure filtration was washed twice with anhydrous methanol, with the amount of methanol used in each wash being 15% to 20% of the wet mass. The synthetic pressure filtrate is mixed with methanol washing waste liquid, and after filtration to remove impurities, adjustment of the alcohol-water ratio, and pH calibration, a recycled liquid is obtained, with an overall recycling rate of ≥60%.
[0020] Preferably, the drying process is vacuum drying, with a drying temperature ≤55℃ and a gauge pressure of -0.08MPa; the compounded alcohol ether additive is composed of propylene glycol methyl ether and polyethylene glycol monobutyl ether in a mass ratio of 1:1, and the additive is completely dissolved in anhydrous methanol beforehand, with the total amount of additive added being 0.5% of the wet weight of sodium dithionite; nitrogen is used as the atomizing carrier gas, a dual-fluid nozzle is selected, and the atomization pressure is 0.3MPa~0.5MPa to spray the additive solution evenly onto the surface of the wet product.
[0021] Preferably, the finished product blending process is as follows: the product after vacuum drying is cooled to below 50°C, anhydrous sodium carbonate is added as a stabilizer for blending, and the product is obtained by sieving and sealing and packaging.
[0022] This invention has the following beneficial effects: through the synergistic effect of multiple technologies such as suspension homogenization, multi-point pH control, ethylene oxide suppression, gradient crystallization, and compound alcohol ether additives for particle enlargement, a synergistic effect is produced, which has outstanding inventiveness and practicality. The specific beneficial effects are as follows: through the combination of raw material crushing, semi-insertion of the bottom tube, and enhanced stirring, the solid-liquid separation of the suspension is completely eliminated, the crystal nuclei are pure and uniform in the early stage of synthesis, the crystal density is increased by 40%, the problem of raw material impurities is eliminated, and the basic purity of the product is increased by 4 to 5 percentage points.
[0023] By using ethylene oxide, the sodium thiosulfate in the synthetic pressure filtrate is stably controlled below 3.0 g / L. Multi-point distributed dripping reduces pH fluctuations to ±0.2, locking in the optimal range of 4.4 to 4.6, completely eliminating the risk of catalytic decomposition. The raw material conversion rate is increased from the traditional 70.2% to over 88%. Combined with an over-temperature and over-pressure interlock alarm device, over-temperature and over-pressure safety accidents are prevented.
[0024] The product of this invention has a D50 ≥ 120μm. Standard sieving tests were used to verify the particle size. A CNC standard inspection sieving machine was employed for particle size analysis. The sieve configuration was 100 mesh on the top and 200 mesh on the bottom. Vibration sieving was performed for 5 minutes, with a single sample size of 100.00g. The original sieving data were: 81.28g of material retained on the 100-mesh sieve, 96.43g on the 200-mesh sieve, and 3.57g of material passing through the 200-mesh sieve. Calculations showed that ≥ 200-mesh Class A large particles accounted for 96.43%, meeting the requirement of ≥ 80%, thus conforming to the definition of large particle products. Gradient crystallization combined with compound alcohol ether additives and agglomeration technology significantly reduced the product's specific surface area, achieving a dust suppression rate ≥ 95%, with no significant dust generation during production and use. The large-particle crystals are less prone to heat accumulation and spontaneous combustion, significantly improving the intrinsic safety level. Fugitive sulfur dioxide emissions approached zero, and all environmental indicators met the standards.
[0025] The compound alcohol ether additives form a stable organic adsorption film. After 18 months of storage at room temperature, the particle integrity rate is ≥96%, and the aggregated structure does not disintegrate. The dense large-particle crystals and sodium carbonate composite stable system extend the shelf life of the finished product from 6 months to more than 12 months under sealed conditions of 25℃ and 50% relative humidity. The reduction efficiency decays slowly during storage, which can meet the needs of long-term storage and high temperature and high humidity conditions in many industries.
[0026] Bont salts circulate in the recycled blending solution without abnormal accumulation over a long period. Synthetic pressure filtration filtrate and methanol washing waste liquid are treated to prepare recycled blending solution, with an overall liquid phase recycling rate of ≥60%. The loss of liquid sulfur dioxide and sodium formate raw materials is reduced, and the overall production cost is reduced by 8% to 12%. The process only requires minor modifications to existing equipment and does not require large-scale replacement of equipment, resulting in low modification costs and suitability for large-scale upgrades of existing domestic production lines. Attached Figure Description
[0027] Figure 1 This is a process flow diagram of a method for preparing large-particle, highly stable sodium hydrosulfite proposed in this invention. Detailed Implementation
[0028] Reference Figure 1 This invention proposes a method for preparing large-particle, highly stable sodium hydrosulfite, integrating five synergistic technologies: raw material pretreatment, suspension homogenization, multi-point distributed pH precision control, ethylene oxide directional inhibition of side effects, gradient temperature-controlled crystallization, and compounded alcohol-ether additives for agglomeration and particle enlargement. The complete process flow consists of six steps: batching, synthesis reaction, crystallization and aging, filtration and washing, drying, and finished product blending. The entire process utilizes industrial high-purity nitrogen for inert protection. The specific technical solution is as follows: (1) Batching process: Suspension preparation and homogenization to prevent stratification pretreatment Abandoning the traditional method of preparing suspensions with sodium carbonate, we use sodium metabisulfite and liquid sulfur dioxide to prepare AME suspension, and sodium formate to prepare AE suspension. We solve the problem of suspension stratification through three methods: raw material crushing, equipment modification, and enhanced stirring.
[0029] Raw material ratio (mass ratio): Sodium formate: Sodium metabisulfite: Liquid sulfur dioxide = 1.2:1:0.8; The reaction medium is a methanol-deionized water mixture, and the mass ratio of methanol to deionized water is strictly controlled at 80:20.
[0030] Preparation of AE suspension (a suspension formed by dispersing sodium formate in a methanol-deionized water mixed medium): Add 60% of the previous batch's recycled blending liquid and industrial-grade sodium formate (the recycled blending liquid is the synthetic pressure filter filtrate obtained by separating wet sodium hydrosulfite from crystallization and aging under nitrogen pressure; this synthetic pressure filter filtrate is then combined with the methanol washing waste liquid after washing the wet product, and after filtration to remove impurities, adjusting the alcohol-water ratio, and calibrating the pH, a recyclable liquid phase is obtained, containing methanol-water solvent, residual raw materials, sodium thiosulfate, Bunter salt, and other dissolved components) to deionized water to adjust the alcohol-water ratio to 80:20, continuously stir and preheat to 65℃.
[0031] Preparation of AME suspension (referring to the suspension formed by dispersing sodium metabisulfite and liquid sulfur dioxide together in a methanol-deionized water mixed medium): Sodium metabisulfite and liquid sulfur dioxide are added to the No. 2 batching vessel, and the pressure is controlled at 0.2MPa~0.3MPa in a sealed manner. The temperature is controlled at ≤15℃ throughout the process to avoid the volatilization of sulfur dioxide.
[0032] Homogenization pretreatment: The agglomerated sodium formate and sodium metabisulfite are pulverized to 80μm~120μm using an air jet mill; the straight bottom pipe of the batching vessel is modified into a semi-bottom discharge pipe, with the discharge pipe opening located in the middle of the axial direction of the batching vessel, so that the uniform solid-liquid material in the middle of the vessel is extracted first when feeding; the stirring speed is 120r / min~150r / min throughout the process to completely eliminate the phenomenon of solid-liquid stratification.
[0033] (2) Synthesis reaction process: inert protection, precise pH control, and targeted suppression of side reactions. The entire synthesis reaction was carried out under an inert nitrogen atmosphere. By combining online pH monitoring, multi-point distributed dropping, and ethylene oxide side-effect suppression technology, the optimal reaction range was determined.
[0034] Pretreatment of the reactor body: The synthesis reactor is purged multiple times with industrial high-purity nitrogen gas with a purity of ≥99.99% until the oxygen content inside the reactor is <0.1%, thus isolating oxygen and preventing the oxidative decomposition of sodium dithionite.
[0035] Reaction parameter control: AE suspension and AME suspension are introduced simultaneously, system temperature is 78℃~83℃, reaction pressure is 0.15MPa~0.25MPa, stirring speed is 80r / min~120r / min, and total feeding time is 2h~3h.
[0036] Precise pH control: The liquid sulfur dioxide is added via a distributed micro-droplet method at 3-5 points instead of a single tube. The dripping tubing is made of corrosion-resistant polytetrafluoroethylene, and the dripping points are evenly distributed along the side wall of the synthesis reactor. This is combined with continuous real-time monitoring using an immersion-type industrial online pH electrode, with a data acquisition frequency of ≥1 time / second, supplemented by manual offline sampling and calibration every 30 minutes. The sulfur dioxide dripping rate is finely adjusted in real time to stabilize the system pH at 4.4-4.6, with pH fluctuations ≤±0.2. A pH warning range of 4.3-4.8 is set; if the parameter exceeds this range, the sulfur dioxide flow rate is immediately adjusted.
[0037] Side reaction suppression: Ethylene oxide is added dropwise at a uniform rate from the initial stage of the synthesis reaction, and all addition is completed within the first 1 / 3 of the total reaction time, according to 1.0 to 1.5 times the stoichiometric ratio of the estimated amount of sodium thiosulfate. This metering method is suitable for continuous industrial production, is not affected by dynamic changes in the volume and mass of the reaction system, and has high metering accuracy.
[0038] Ethylene oxide undergoes an addition reaction with sodium thiosulfate to produce sodium hydroxyethyl thiosulfate (commonly known in the industry as Bont salt). Bont salt is a water-soluble, inert inorganic salt, stable at room temperature and the reaction temperature of this invention. It does not participate in the main reaction, does not precipitate solids, does not interfere with the crystallization process of sodium dithionite, and does not introduce new impurities. The Bont salt in the synthesis pressure filtrate is recycled into the reuse preparation solution. After long-term continuous monitoring, after 60 batches of recycling, the concentration of Bont salt in the reuse preparation solution tends to reach dynamic equilibrium, with no abnormal accumulation. It has no negative impact on the recycling efficiency of the reuse preparation solution or the purity of the product.
[0039] This process ensures that the concentration of sodium thiosulfate in the synthetic filtration filtrate is consistently controlled to ≤3.0 g / L, completely eliminating its catalytic decomposition effect. The concentration of sodium thiosulfate in the synthetic filtration filtrate is determined by iodometric titration.
[0040] The sulfur-containing waste gas generated by the reaction is collected and treated using a combination of alkaline washing and incineration processes. The exhaust gas is discharged at high altitude after passing the test. Solid waste is entrusted to a third party with hazardous waste treatment qualifications for compliant disposal.
[0041] (3) Crystallization and aging process: gradient cooling to enhance crystal density. After feeding, keep the temperature for 30 minutes. Once the pH of the system and the state of the materials have stabilized, slowly cool the temperature to 45℃-50℃ at a gradient of 1℃ / min to 2℃ / min, and then age at this constant temperature for 1 hour. Slow cooling allows the crystal nuclei to grow evenly, improving crystal density and particle uniformity, and avoiding crystal breakage and particle size reduction caused by rapid cooling.
[0042] (4) Filtration and washing process: nitrogen pressure filtration and liquid phase recovery and circulation to reduce raw material loss. The solid-liquid mixture is separated by nitrogen pressure filtration at a pressure of 0.1 MPa to 0.2 MPa to obtain wet sodium dithionite and synthetic filtration filtrate. The wet product is washed twice with anhydrous methanol, with each wash using 15% to 20% of the wet product weight, to remove surface impurities and aqueous solution, resulting in methanol washing waste liquid. The synthetic filtration filtrate and methanol washing waste liquid are recycled together, filtered to remove impurities, adjusted in alcohol-to-water ratio, and calibrated at pH to obtain a recycled liquid. The overall recycling rate is ≥60%, reducing raw material consumption and waste emissions.
[0043] (5) Drying process: spray modification of compound alcohol ether additives and low-temperature vacuum drying. Low-temperature vacuum drying is used to avoid the thermal decomposition of sodium dithionite, while compound alcohol ether additives are introduced to achieve fine particle agglomeration and eliminate dust at the source.
[0044] Drying parameters: gauge pressure -0.08MPa, drying temperature ≤55℃, nitrogen protection throughout the process.
[0045] Additive Preparation and Addition: The compound alcohol ether additive is prepared by compounding propylene glycol methyl ether and polyethylene glycol monobutyl ether in a 1:1 mass ratio. This additive is neutral and does not chemically react with sodium dithionite under low temperature conditions at 55℃ and below, or in methanol medium. It exhibits good compatibility and stability and will not introduce organic impurities. After the additive is completely dissolved in anhydrous methanol, it is sprayed evenly onto the surface of the wet product. The total amount of additive added is 0.5% of the wet product weight.
[0046] Explanation of the long-term stability of the additives: Propylene glycol methyl ether and polyethylene glycol monobutyl ether molecules can form a dense organic adsorption film on the surface of sodium dithionite crystals, achieving physical agglomeration of fine particles through intermolecular van der Waals forces; both types of alcohol ether substances have boiling points above 120℃, ensuring that the organic film will not fail due to the volatilization of the additives themselves under low-temperature drying conditions of ≤55℃ and normal temperature storage conditions; at the same time, the controlled condition of sodium thiosulfate ≤3.0g / L in the synthesis pressure filtration filtrate avoids the decomposition of impurities in the system and the generation of gas that breaks the agglomerated organic film on the particle surface. The organic film can also isolate air and trace acidic substances from contact with the crystals and will not be destroyed by sulfur dioxide generated by the trace decomposition of sodium dithionite. After 18 months of sealed storage at room temperature, the product particle structure remained intact, with no pulverization or disintegration, and the agglomeration effect was long-term and stable.
[0047] The additives can form a flexible bonding layer on the crystal surface, using intermolecular forces to cause fine particles to agglomerate into large particles.
[0048] (6) Finished product blending process: stabilization treatment, screening and packaging After drying, the product is cooled to below 50°C, and anhydrous sodium carbonate is added as a stabilizer for blending to further improve the product's storage stability. The particle size of the finished product is screened using a CNC standard inspection sieve machine. The screening conditions are: 100-mesh sieve on the upper layer, 200-mesh sieve on the lower layer, vibrating sieve for 5 minutes, and 100.00g of sample is taken at a time. After screening, the product is sealed and packaged to obtain large-particle sodium dithionite finished product.
[0049] Working principle: The principle of suspension homogenization: raw material crushing eliminates the problem of agglomeration, the bottom tube is partially inserted to extract the uniform material in the middle and feed it in, and high-speed stirring is used to make the solid and liquid phases of the AE and AME suspension uniformly distributed. In the early stage of synthesis, the crystal nuclei are pure and uniform in size, avoiding crystal decomposition caused by impurities in the raw materials and excessive local acidity.
[0050] The principle of precise pH control: Liquid sulfur dioxide is added dropwise at multiple points to avoid a sudden increase in local acid concentration caused by single-point feeding. Combined with online real-time pH monitoring, the system is locked in the optimal range of 4.4 to 4.6. Within this range, the main reaction rate is stable, the probability of sodium dithionite decomposition is the lowest, and the crystal growth is dense.
[0051] Side reaction inhibition principle: Sodium thiosulfate, generated by the trace decomposition of sodium dithionite, has a strong catalytic effect and will accelerate the decomposition of the main product; Ethylene oxide reacts specifically with sodium thiosulfate to generate water-soluble inert Bunter salt, which blocks the catalytic chain, controls the concentration of by-products within a safe range, and ensures the efficient progress of the main reaction.
[0052] The principle of particle thickening and stabilization: Gradient cooling aging allows crystal nuclei to grow fully, increasing the intrinsic particle size of the crystals; compound alcohol ether additives fill the gaps between fine particles during the drying process, achieving fine powder agglomeration, increasing particle size, and reducing specific surface area; the organic film formed by the additives has anti-volatilization and anti-reaction properties, ensuring that the particles do not disintegrate over a long period of time; sodium carbonate stabilizer can neutralize trace acidic substances, inhibit oxidative decomposition during storage, and extend shelf life.
[0053] Synergistic mechanism of multiple technologies: The coupling of various technologies produces new comprehensive effects: Homogenization of the suspension ensures the quality of the initial crystal nuclei, laying the foundation for the formation of large, dense crystals; precise pH control stabilizes the main reaction and inhibits the decomposition of sodium dithionite on the one hand, and maintains sodium thiosulfate at a low concentration range with the help of ethylene oxide, thus doubly blocking side reactions; low concentration of sodium thiosulfate provides an environment for normal crystal growth, and gradient crystallization further optimizes the crystal morphology; finally, the compound alcohol ether additive completes particle agglomeration and builds a long-term stable structure; with the synergy of multiple technologies, the product simultaneously achieves high purity, large particles, low dust, low by-products, long storage period, and no particle pulverization.
[0054] All raw materials used in this invention are industrial grade. The equipment selected is a conventional 1000L stainless steel pressure reactor, batching vessel, air jet mill, vacuum dryer, industrial online pH meter, laser particle size analyzer, and CNC standard inspection and screening machine. All units used in the process are international standard units.
[0055] Standardized testing conditions: ambient temperature 25℃, relative humidity 50%; 1. Particle size analysis: A 200-mesh particle size analyzer (200-mesh sieve aperture 74μm, oversize material is defined as Grade A large particles) and a laser particle size analyzer were used to detect the median particle size D50; Supporting experimental specifications for sodium hydrosulfite particle size sieving: The experimental equipment is a CNC standard inspection sieve machine, with a 100-mesh upper layer and a 200-mesh lower layer sieve, a vibrating sieve duration of 5 minutes, and a single sample size of 100.00g. After sieving, the mass of the 100-mesh, 200-mesh, and 200-mesh oversize materials were weighed respectively, and the proportion of each particle size range was calculated. 2. Dust suppression rate: The test was conducted in accordance with the "Determination of Total Dust Concentration in Workplace Air" (GBZ / T192.1~2007), and samples were taken from the batching, drying, and discharging stations for calculation. 3. Sodium thiosulfate concentration: determined by iodometric titration; 4. Shelf life and particle stability: Store in sealed packaging at room temperature, and periodically test purity and particle size distribution; 5. The entire reaction system is equipped with an over-temperature and over-pressure interlock alarm device. When the reaction temperature is >85℃ or the pressure is >0.3MPa, the feed will be automatically cut off to ensure production safety. Example 1
[0056] 1. Ingredient preparation process Raw materials: 485 kg sodium formate, 405 kg sodium metabisulfite, 325 kg liquid sulfur dioxide; methanol to deionized water mass ratio 80:20.
[0057] Sodium formate and sodium metabisulfite were pulverized to 100 μm using an air jet mill. In batching vessel No. 1, 60% of the total system volume of the previous batch of recycled preparation solution and 485 kg of sodium formate were added, and deionized water was added to adjust the alcohol-to-water ratio to 80:20. The mixture was stirred and preheated to 65°C to prepare an AE suspension. In batching vessel No. 2, 405 kg of sodium metabisulfite and 325 kg of liquid sulfur dioxide were added, and the pressure was controlled at 0.25 MPa and the temperature at 12°C to prepare an AME suspension. Both batching vessels used semi-inserted bottom discharge pipes, and the stirring speed was 130 r / min.
[0058] 2. Synthesis reaction process The synthesis reactor was purged with high-purity nitrogen (≥99.99%), resulting in an oxygen content of 0.08%. Simultaneously, AE and AME suspensions were introduced, maintaining a temperature of 80℃, a pressure of 0.20 MPa, and a stirring speed of 100 r / min, with a total feeding time of 2.5 hours. Liquid sulfur dioxide was added via a 4-point distributed dripping system using PTFE (polytetrafluoroethylene) piping. An online pH meter was used for sampling and calibration every 30 minutes, maintaining a stable pH between 4.45 and 4.55. Ethylene oxide was added at a uniform rate from the initial stage of synthesis, completing the addition within the first 50 minutes (one-third of the 2.5-hour feeding period). The ethylene oxide dosage was based on a stoichiometric ratio of 1.2 times the estimated sodium thiosulfate production. Throughout the synthesis, the sodium thiosulfate concentration in the filtrate was maintained between 2.4 g / L and 2.9 g / L. Sulfur-containing waste gas was treated by alkaline scrubbing and incineration before being discharged in compliance with emission standards.
[0059] 3. Crystallization and aging process After adding the ingredients, keep warm for 30 minutes, then cool down to 48℃ at a rate of 1.5℃ / min, and age at a constant temperature for 1 hour.
[0060] 4. Filtration and washing process Nitrogen pressure filtration at a pressure of 0.15 MPa yields wet sodium dithionite and synthetic filtrate. The product is then washed twice with anhydrous methanol, with each wash using 18% of the wet product's weight. This yields methanol washing waste liquid. The synthetic filtrate and methanol washing waste liquid are recovered, filtered to remove impurities, and adjusted according to parameters to obtain a recycled blending solution with a recycling rate of 62%.
[0061] 5. Drying process Vacuum drying at 52℃ and gauge pressure -0.08MPa; propylene glycol methyl ether and polyethylene glycol monobutyl ether are compounded in a 1:1 ratio, and 0.5% of the total mass of the wet product is taken as the compounding agent, completely dissolved in anhydrous methanol and sprayed onto the surface of the wet product. After drying, the product is discharged.
[0062] 6. Finished product blending process The material was cooled to 46℃, and anhydrous sodium carbonate was added and mixed. A particle size sieving test was carried out: 100.00g of the finished product was taken and vibrated for 5 minutes using a CNC sieve. 81.28g was retained by a 100-mesh sieve, 96.43g by a 200-mesh sieve, and 3.57g was passed through the 200-mesh sieve. The proportion of large particles ≥200 mesh was 96.43%. The product was then sieved, sealed, and packaged to obtain the finished product. Example 2
[0063] Fine-tuning parameters: synthesis temperature 78℃, pH control 4.4~4.5, aging temperature 45℃, ethylene oxide addition amount is 1.0 times the stoichiometric ratio of the estimated sodium thiosulfate production, and the rest of the operation is the same as in Example 1; the finished product sieve test shows that ≥200 mesh particles account for 83%. Example 3
[0064] Fine-tuning parameters: synthesis temperature 83℃, pH control 4.5~4.6, aging temperature 50℃, ethylene oxide addition amount 1.5 times the stoichiometric ratio of the estimated sodium thiosulfate production, and other operations are consistent with Example 1; finished product sieve testing showed that ≥200 mesh particles accounted for 85%.
[0065] Comparative Example 1 (Traditional Sodium Formate Process) The traditional sodium carbonate suspension was prepared, sulfur dioxide was added dropwise through a single tube, and there was no raw material crushing or suspension homogenization treatment, no additive modification, and conventional drying process. The raw material ratio, reaction temperature, and pressure were completely consistent with those in Example 1; the proportion of particles ≥200 mesh in the finished product was only 41%.
[0066] Comparative Example 2 (only pH adjustment and ethylene oxide were used to suppress side effects; no suspension homogenization or granulation with additives were used). The invention retains the precise pH control and ethylene oxide suppression technology, but removes the raw material crushing, semi-insertion tube, and compound alcohol ether additives. The remaining parameters are the same as in Example 1; the finished product has 45% particles with a mesh size of ≥200 mesh.
[0067] Comparative Example 3 (only suspension homogenization and particle enlargement with additives were used, without precise pH control and ethylene oxide side effect suppression) The suspension homogenization and compound alcohol ether additive technology of this invention are retained, and the traditional single-tube dripping is used without adding ethylene oxide. The remaining parameters are the same as in Example 1; the proportion of particles ≥200 mesh in the finished product is 72%.
[0068] Performance data comparison table (adds D50 particle size and 18-month particle stability index)
[0069] Particle size description: The aperture of a 200-mesh sieve is 74μm. This invention defines large-particle sodium dithionite as having a D50 ≥ 120μm and a material content ≥ 80% on a 200-mesh sieve. This invention provides standardized sieving test records as the basis for product particle size determination. The sieving equipment, sampling amount, and sieving time are fixed, ensuring strong data repeatability and serving as a standard for product factory testing.
[0070] Specific implementation notes: 1. The entire process must be protected by industrial high-purity nitrogen gas with a purity of ≥99.99%. Sodium dithionite wet product and dried finished product must not be exposed to air for a long time to prevent oxidation and decomposition.
[0071] 2. Liquid sulfur dioxide and ethylene oxide are flammable, explosive, and toxic hazardous chemicals. The workshop must be equipped with explosion-proof and electrostatic protection facilities, and materials must be transported in a closed system. The workshop must also be equipped with tail gas alkaline washing and incineration treatment devices to ensure that the exhaust gas meets emission standards.
[0072] 3. The online pH meter performs a sampling test every 30 minutes. Once the pH exceeds the warning line of 4.3-4.8, the sulfur dioxide drop acceleration rate is immediately fine-tuned to stabilize the reaction system.
[0073] 4. Compound alcohol ether additives must be completely dissolved in anhydrous methanol before spraying to prevent local additive accumulation and excessive particle adhesion.
[0074] 5. The recycled preparation solution needs to be filtered regularly to remove impurities, and the alcohol-to-water ratio and pH value need to be calibrated to avoid the accumulation of impurities after long-term circulation, which would affect product quality; the concentration of Bond salt in the recycled preparation solution should be monitored regularly to maintain dynamic balance.
[0075] 6. The system's over-temperature and over-pressure interlock alarm devices need to be calibrated regularly to ensure that the emergency protection functions are operating normally.
[0076] 7. Before leaving the factory, all finished products undergo particle size screening and testing. The screening test is carried out in strict accordance with the specifications. Products that fail the screening are remixed and processed to ensure that the large particle size index of each batch of products consistently meets the standards.
[0077] 8. Monitor the concentration of Bont salt during the recycling process of the reusable preparation solution. Discharge a portion of the reusable preparation solution every 15-20 batches and replenish it with fresh alcohol-water medium to prevent Bont salt from saturating and precipitating out.
[0078] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing large-particle, highly stable sodium hydrosulfite, characterized in that, The process includes the batching process, the synthesis reaction process, the crystallization and aging process, the filtration and washing process, the drying process, and the finished product blending process. The entire process is protected by nitrogen inert gas, and the reaction medium is a mixture of methanol and deionized water with a mass ratio of 80:
20. The ingredient preparation process involves preparing AME suspension with sodium metabisulfite and liquid sulfur dioxide, and preparing AE suspension with sodium formate. The two suspensions are then subjected to homogenization and anti-stratification pretreatment. The synthesis reaction process employs online pH monitoring combined with a multi-point distributed dropping method to control the pH of the reaction system to 4.4–4.6, while simultaneously adding ethylene oxide to the reaction system. The ethylene oxide is added at 1.0–1.5 times the stoichiometric ratio of the estimated sodium thiosulfate production, controlling the sodium thiosulfate concentration in the synthesis filter press filtrate to 3.0 g / L or below. The estimated sodium thiosulfate production is determined based on the theoretical calculation value of a main reaction by-product rate of 3%–5%, or by real-time back-calculation based on the measured sodium thiosulfate concentration in the previous batch synthesis filter press filtrate. The drying process involves adding a compound alcohol ether additive to the wet sodium dithionite to increase the particle size of the product and reduce dust generation.
2. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 1, characterized in that, In the batching process, the raw materials are in the following mass ratio: sodium formate: sodium metabisulfite: liquid sulfur dioxide = 1.2:1:0.8; When preparing AE suspension, add 60% of the previous batch of recycled preparation liquid and industrial-grade sodium formate to No. 1 batching vessel, add deionized water to adjust the alcohol-water ratio to 80:20, stir and preheat to 65°C. When preparing the AME suspension, sodium metabisulfite and liquid sulfur dioxide are added to the No. 2 batching vessel, and the pressure inside the vessel is controlled at 0.2MPa~0.3MPa and the system temperature is ≤15℃.
3. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 2, characterized in that, The suspension homogenization and anti-stratification pretreatment includes: using an air jet mill to crush the agglomerated sodium formate and sodium metabisulfite, with the raw material particle size controlled at 80μm to 120μm; modifying the traditional straight-insertion bottom pipe of the batching vessel into a semi-insertion bottom discharge pipe, with the discharge pipe outlet installed at 1 / 3 to 1 / 2 of the static liquid level in the vessel; prioritizing the extraction of the suspension from the uniform solid-liquid region in the middle of the batching vessel during the synthesis feeding stage; and maintaining the stirring speed at 120r / min to 150r / min throughout the process.
4. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 3, characterized in that, The synthesis reaction process is carried out in a stainless steel pressure reactor, which is pre-purified with industrial high-purity nitrogen with a purity of ≥99.99% until the oxygen content inside the reactor is <0.1%. Simultaneously, AE suspension and AME suspension are introduced into the synthesis reactor, and the reaction system temperature is controlled at 78℃~83℃, the reaction pressure at 0.15MPa~0.25MPa, the stirring speed at 80r / min~120r / min, and the total feeding time is 2h~3h.
5. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 4, characterized in that, The multi-point distributed dripping method is as follows: the liquid sulfur dioxide is changed from the traditional single-tube dripping to a 3-5 point distributed micro-dripping method. The dripping pipeline is made of corrosion-resistant polytetrafluoroethylene, and the dripping points are evenly distributed along the side wall of the synthesis reactor. The immersion industrial online pH electrode is used for continuous real-time monitoring. Manual sampling is required every 30 minutes. The pH is also tested during sampling. The sulfur dioxide drop acceleration rate is finely adjusted in real time to control the pH fluctuation range of the reaction system within ±0.
2. The production process is set with a pH warning range of 4.3 to 4.
8. When the pH exceeds this warning range, the acceleration rate of liquid sulfur dioxide droplets is adjusted immediately.
6. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 5, characterized in that, The ethylene oxide is added dropwise at a uniform rate from the initial stage of the synthesis reaction, and all addition is completed within the first 1 / 3 of the total reaction time. The ethylene oxide reacts with sodium thiosulfate to form Bunter salt, which blocks the catalytic decomposition of sodium dithionite by sodium thiosulfate.
7. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 6, characterized in that, The crystallization and aging process is as follows: after the synthesis reaction is completed, the temperature is kept for 30 minutes. After the pH value stabilizes and no longer changes, the temperature is slowly reduced to 45℃~50℃ at a rate of 1℃ / min~2℃ / min, and the temperature is kept constant for 1 hour to promote the full growth and densification of sodium dithionite crystals.
8. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 7, characterized in that, The filtration and washing process uses nitrogen pressure filtration to separate the solid wet product from the synthetic pressure filtrate, with a pressure of 0.1 MPa to 0.2 MPa. The wet sodium dithionite after pressure filtration was washed twice with anhydrous methanol, with the amount of methanol used in each wash being 15% to 20% of the wet mass. The synthetic pressure filtrate is mixed with methanol washing waste liquid, and after filtration to remove impurities, adjustment of the alcohol-water ratio, and pH calibration, a recycled liquid is obtained, with an overall recycling rate of ≥60%.
9. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 8, characterized in that, The drying process is vacuum drying, with a drying temperature ≤55℃ and a gauge pressure of -0.08MPa; the compound alcohol ether additive is composed of propylene glycol methyl ether and polyethylene glycol monobutyl ether in a mass ratio of 1:
1. The additive is completely dissolved in anhydrous methanol beforehand, and the total amount of additive added is 0.5% of the wet weight of sodium dithionite.
10. The method for preparing a large-particle, highly stable sodium hydrosulfite according to claim 9, characterized in that, The finished product blending process is as follows: after vacuum drying, the product is cooled to below 50°C, anhydrous sodium carbonate is added as a stabilizer for blending, and after sieving and sealing, sodium dithionite is obtained as the finished product.